2018
DOI: 10.18174/458060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reducing dietary crude protein in hog finisher barrows and gilts on technical performance

Abstract: of op www.wur.nl/livestock-research (onder Wageningen Livestock Research publicaties).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The energy value (EW) of the basal diets was 1.12, 1.10 and 1.10 for the starter, grower and finisher diet, respectively. The levels of supplementation of EAA in the I diets (Lys, Met, Thr, Trp, Val and Ile) were calculated with the factorial model using a starter diet with 165 g/kg CP based on barley, corn and soya bean meal as a reference (Pluk and van Krimpen, 2018) for the starter diets and the respective grower and finisher "B" diets in the present study for the grower and finisher diets, respectively.…”
Section: Growing and Finishing Pigsmentioning
confidence: 99%
“…The energy value (EW) of the basal diets was 1.12, 1.10 and 1.10 for the starter, grower and finisher diet, respectively. The levels of supplementation of EAA in the I diets (Lys, Met, Thr, Trp, Val and Ile) were calculated with the factorial model using a starter diet with 165 g/kg CP based on barley, corn and soya bean meal as a reference (Pluk and van Krimpen, 2018) for the starter diets and the respective grower and finisher "B" diets in the present study for the grower and finisher diets, respectively.…”
Section: Growing and Finishing Pigsmentioning
confidence: 99%
“…Ingredient and nutrient composition of the starter diet used for model calculations (Pluk and van Krimpen, 2018…”
Section: Trauma Immune System Activation and Whole Body Protein Turnmentioning
confidence: 99%
“…Reference scenario (with no health challenge): Protein deposition (PD) in the body is determined by the post-absorptive availability of essential amino acids provided via a reference diet. PD under this condition is equal to PDmax, the maximum (genetic) PD of the pig weighing 50 kg and assuming the dietary supply of energy is not limiting PD in this condition.Reference diet: a barley, maize, soybean meal based starter diet which was evaluated byPluk and van Krimpen (2018). The reference diet contained 165 g/kg CP and 9.3 g/kg SID Lys and was supplemented with free Lys, Met, Thr, Trp and Val to balance its AA profile relative to Lys (Appendix 3). The amino acid requirements for maintenance purposes (basal protein turnover, integument losses, basal endogenous amino acid losses at ileal level) are taken from INRAPORC (van Milgen et al, 2008) (Appendix 5).…”
mentioning
confidence: 99%
“…Latin American, and thus in reducing the amount of non-EU protein in the diet. Studies with broilers and growing-finishing pigs, also conducted within the framework of Feed4Foodure, showed that it was possible in low-protein -free AA supplemented diets to reduce 20 to 40% of the original SBM, without compromising animal performance (Van Harn et al, 2017;Pluk and Van Krimpen, 2018).…”
Section: Introductionmentioning
confidence: 99%